2006
DOI: 10.1097/01.hjh.0000244961.69985.05
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antihypertensive drug therapy and cognitive function in elderly hypertensive patients with memory complaints

Abstract: Antihypertensive therapy was associated with a lower risk of cognitive impairment and AD. In particular, the use of calcium antagonists was associated with a decreased risk of cognitive impairment and AD independently of the blood pressure level, suggesting a specific neuroprotective effect of these antihypertensive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 37 publications
3
41
1
2
Order By: Relevance
“…Additionally, a 1-decade follow-up study (2000 to 2010), involving 82,107 hypertensive patients of more than 60 years of age, demonstrated that prescription of L-type CCBs during antihypertensive therapy reduces risk of dementia in these patients, indicating that these pharmaceuticals could be clinically used to treat Alzheimer´s disease [16]. These findings for the neuroprotective CCBseffects have been demonstrated in 1,241 elderly hypertensive patients with memory impairment [17]. The prescription of CCBs decreased the risk of cognitive impairment, and Alzheimer´s disease, independently of blood pressure levels when compared to patients not receiving CCBs [17].…”
Section: + /Camp Signalling Interaction and The Neuroscience Fieldmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, a 1-decade follow-up study (2000 to 2010), involving 82,107 hypertensive patients of more than 60 years of age, demonstrated that prescription of L-type CCBs during antihypertensive therapy reduces risk of dementia in these patients, indicating that these pharmaceuticals could be clinically used to treat Alzheimer´s disease [16]. These findings for the neuroprotective CCBseffects have been demonstrated in 1,241 elderly hypertensive patients with memory impairment [17]. The prescription of CCBs decreased the risk of cognitive impairment, and Alzheimer´s disease, independently of blood pressure levels when compared to patients not receiving CCBs [17].…”
Section: + /Camp Signalling Interaction and The Neuroscience Fieldmentioning
confidence: 86%
“…These findings for the neuroprotective CCBseffects have been demonstrated in 1,241 elderly hypertensive patients with memory impairment [17]. The prescription of CCBs decreased the risk of cognitive impairment, and Alzheimer´s disease, independently of blood pressure levels when compared to patients not receiving CCBs [17]. These findings highlight the concept that attenuation of cytosolic Ca 2+ overload produced by L-type CCBs due to blockade of Ca 2+ influx could be a successful pharmacological strategy to reduce, or prevent, neuronal death in neurodegenerative diseases.…”
Section: + /Camp Signalling Interaction and The Neuroscience Fieldmentioning
confidence: 87%
“…The use of particular antihypertensive medications, specifically the DHPs nitrendipine and nilvadipine, have been associated with a reduced risk of developing dementia, including AD (7,8,10,16,33). We therefore investigated the effects of several clinically used antihypertensive DHPs as well as non-DHP CCBs on Aβ production as this peptide is believed to be central to the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study of 1617 elderly African-American subjects followed for 5 years, indicated a signifi cant 38% decrease in cognitive decline in treated hypertensive subjects compared with untreated subjects (OR = 0.62, 95% CI = 0.45-0.84) (Murray et al 2002). Moreover, a recent study found that in a sample of 1241 elderly patients, the odds ratio for AD was 0.58 (95% CI = 0.42-0.81) in treated compared with untreated hypertensive patients (Hanon et al 2006). Lastly, the recent Cache County Study performed in 3,308 people (Mean age 75 years), followed up 3 years, indicated a signifi cant reduction of the risk of AD from 36% (OR = 0.64, 95% CI = 0.41-0.98) (Khatchaturian et al 2006).…”
Section: Hypertension and Cognitive Declinementioning
confidence: 99%